Coexistence of schizophrenia and epilepsy: record-linkage studies. - Wotton, C; Goldacre, M (2012)
For many years, there has been interest in a possible link between epilepsy and schizophrenia. A recent study found a strong, bidirectional link between the two conditions: people with one had a higher than average risk of having the other. Using two large data sets of hospital admission data, we investigated whether schizophrenia and epilepsy occur together in individuals more commonly than expected by chance. We undertook a retrospective cohort study using the Oxford Record Linkage Study (ORLS) and English national linked Hospital Episode Statistics to investigate the coexistence of these conditions. There was an elevated risk of epilepsy in people admitted to hospital with schizophrenia (ORLS rate ratio 2.1, 95% confidence interval 1.6-2.6; England 3.0, 2.9-3.1) and an elevated risk of schizophrenia in people admitted to hospital with epilepsy (ORLS 5.1, 4.1-6.2; England 4.5, 4.3-4.6). We found no consistent difference between male and female patients. Schizophrenia and epilepsy occur together in individuals more frequently than expected by chance.